Rituximab for the treatment of connective tissue disease–associated interstitial lung disease: A systematic review and meta-analysis - Xu, Linrui; Wang, Faping; Luo, Fengming (Frontiers in Pharmacology, 2022)
Background: Interstitial lung disease (ILD) is a common pulmonary disease often associated with significant morbidity and mortality in patients with connective tissue diseases (CTD). Currently, no gold-standard therapies are available for CTD-ILD. Recently, several studies have proposed that rituximab (RTX) may be effective for the treatment of CTD-ILD. Objectives: This study aimed to systematically evaluate the efficacy and safety of RTX for the treatment of CTD-ILD. Methods: Studies were selected from PubMed, Embase, and Cochrane Library, up to July 20, 2022. Improvement and stable rates were extracted as the main outcomes and pooled using the weighted mean proportion with fixed or random-effects models, in case of significant heterogeneity (I2>50%). Safety analysis was performed based on the adverse events reported in all of the studies. Results: Thirteen studies (312 patients) were included in the meta-analysis. The follow-up durations ranged from 6-36 months. The pooled improvement rate was 35.0% (95% CI: 0.277–0.442), while the pooled stable rate was 59.2% (95% CI: 0.534–0.656). Anti-synthetase syndrome associated with ILD (ASS-ILD, 48.1% (95% CI, 0.373–0.620)) and idiopathic inflammatory myopathies associated with ILD (IIM-ILD, non-ASS, 47.4% (95% CI, 0.266–0.846)) had higher improvement rates than the other types. A total of 106 adverse events associated with RTX or progressive ILD were reported among the 318 patients, 55.7% of which were mild. Among 19 deaths, 17 were due to ILD progression, one to severe pulmonary arterial hypertension, and one to Pneumocystis jirovecii infection. Conclusion: RTX, which exhibits a satisfactory safety profile, is an effective treatment option for CTD-ILD, even in patients who fail to respond to other therapies. Further randomized trials are needed to assess the efficacy of rituximab compared to other treatments for CTD-ILD.